LEGAL STRENGTH OF FIDUSIA POST-DECISION COURT DECISION NUMBER 18/PUU-XVII-2019 ABOUT FIDUSIAN GUARANTEE - Irwan Saputra (Riau Law Journal, 2020)
Not long ago, the Constitutional Court issued a decision in a judicial review case on Law Number 42 of 1999 concerning Fiduciary Guarantee. The articles petitioned for review in the case are Article 15 paragraph (2) and (3) of the Fiduciary Guarantee Law which regulates the executorial power of fiduciary certificates and execution parates. This paper discusses the legal strength of fiduciary guarantees after the Constitutional Court decision Number 18 / PUU-XVII-2019 concerning Fiduciary Guarantee. The research method is normative legal research, especially research using the criteria for the level of legal synchronization, the researcher collects data consisting of secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. The data collection technique is literature review. The data analysis was done qualitatively and draw conclusions from the writer using deductive thinking method. The conclusion is that the Constitutional Court Decision Number 18 of 2019 will have little or more implications for the auction business process conducted by KPKNL. This is because Article 15 paragraph (2) and paragraph (3) of the Fiduciary Law, according to the Constitutional Court Decision Number 18 of 2019, are fundamental norms. Ideally, the execution of fiduciary collateral is through an auction which can only be carried out by KPKNL. The author's suggestion needs supervision by the fiduciary recipient of fiduciary collateral controlled by the debtor. So that the weaknesses in the implementation of legal protection for creditors in a peace agreement are caused by, among others, regulations that give creditors a weak position.